Inverse Kinematical Solving and Trajectory Planning of Redundant Manipulator - Mingsong Zhang; Jinzhi Xiao; Enheng Wang; Qiao Zhuang (Jixie chuandong)
In order to solve the problem of multiple solutions in inverse kinematics of redundant manipulator，taking the 7DOF-S universal manipulator of Jaco2 as the object，an inverse kinematics algorithm combined with analysis and geometry based on coordinate transformation is proposed. According to the geometry structure of the manipulator，the unique solution of the middle angle is derived，and the other joint angles are obtained by mapping. It is verified by Matlab Robotic Toolbox and Simulink modules that the algorithm has high accuracy and operation efficiency. Based on the verified kinematics model，a quintic interpolation algorithm based on rough and accurate interpolation is proposed. The calculation results of trajectory planning verified by Matlab show that the continuity and stability of each joint rotation are better.